2015
DOI: 10.5964/jnc.v1i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Student Magnitude Knowledge of Negative Numbers

Abstract: Numerous studies have demonstrated the relevance of magnitude estimation skills for mathematical proficiency, but little research has explored magnitude estimation with negative numbers. In two experiments the current study examined middle school students' magnitude knowledge of negative numbers with number line tasks. In Experiment 1, both 6th (n = 132) and 7th grade students (n = 218) produced linear representations on a -10,000 to 0 scale, but the 7th grade students' estimates were more accurate and linear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
17
2
Order By: Relevance
“…To our knowledge, our study is the first to study the neural basis of mapping both positive and negative numbers onto space. We are aware of only two previous behavioral line-marking experiments using both positive and negative numbers ( Young & Booth, 2015;Ganor-Stern & Tzelgov, 2008). Because the effects of range on spatial bias and landmarking behavior were not the focus of either article, it is not possible to extract strong conclusions about these topics.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, our study is the first to study the neural basis of mapping both positive and negative numbers onto space. We are aware of only two previous behavioral line-marking experiments using both positive and negative numbers ( Young & Booth, 2015;Ganor-Stern & Tzelgov, 2008). Because the effects of range on spatial bias and landmarking behavior were not the focus of either article, it is not possible to extract strong conclusions about these topics.…”
Section: Introductionmentioning
confidence: 99%
“…This logarithmic‐to‐linear shift extends to larger number ranges and older people. Middle school students’ estimates of integers in the negative range −10,000 – 0 and the combined range −1,000 – 1,000 are linear, though with lower accuracy for negative numbers (Young & Booth, ). Adults’ estimates of integers in the combined range −100 – 100 are linear and show comparable accuracy for positive and negative numbers (Ganor‐Stern & Tzelgov, ).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that practice and experience help to integrate negative numbers into an extended mental number line. In addition, Young and Booth ( 2015 ) found results both in line with an extended MNL and in line with a rule-based MNL account in two pointing experiments with middle school students. The authors concluded that this conflicting pattern could reflect under-developed number knowledge and differences in previous number exposure.…”
Section: Evidence From Other Methodsmentioning
confidence: 77%